(untitled) (Journal of Oriental Studies, 2016)
The article discusses principles of systematization of borrowing in assimilation level of Hindi language. There is also given lexical-semantic classification of Arabic, Persian and Turkic borrowings in Hindi and identification of their lingua-cultural and ethno-cultural characteristics. The paper explains the reasons for borrowing and the level of assimilation.